From HRM practices to the practice of HRM: setting a research agenda. Issue 2 (27th May 2014) - Björkman, Ingmar; Ehrnrooth, Mats; Mäkelä, Kristiina; Smale, Adam; Sumelius, Jennie
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to develop an "HRM-as-practice" research agenda. The authors suggest that the HRM-performance literature would benefit from an actor-centric approach and a focus on activities, and that the HR roles research needs to shift its attention toward a more dynamic perspective of HR work and link this further to performance. Design/methodology/approach – The paper first provides an overview of strategy-as-practice (SAP) literature, and then review how extant HRM literature deals with three core notions of SAP: practices, praxis and practitioners. Based on this, the paper outlines an "HRM-as-practice" research agenda. Findings – Focussing on the intersections between praxis, practitioners and practice, the paper suggests that an "HRM-as-practice" approach can give new insights into first, how people-related decisions are made, implemented and enacted in organizations; second, how employees and other HRM stakeholders interpret and engage with HRM; third, how HR actors become more effective and influential organizational agents; and fourth, what the short-term and long-term effects of these actions and activities are. Research limitations/implications – The authors acknowledge the fuzzy and intertwined nature of the practices, practitioners and praxis categories, but believe that their intersections provide a fruitful theoretical lens to examine the practice of HRM. Originality/value – The authors use the HRM-as-practice lens to suggest novel research approaches that can shed new light on several open questions within the HRM field.